2018
DOI: 10.13057/nusbiosci/n100310
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of dietary palm date pits in all-male Nile tilapia (Oreochromis niloticus) diets

Abstract: Swar NMS, Mohamed AHW. 2018. Incorporation of dietary palm date seeds in all-male Nile tilapia (Oreochromis niloticus) diets. Nusantara Bioscience 10: 193-202. The study utilizes a 45-days randomized factorial design 3×2, three levels (25, 50 and 75%) of palm date seeds, three levels (non, with and without) of 3% bakery yeast (Saccharomyces cerevisiae) and three replicates. The observation was carried out in twenty-one plastic aquaria. All-male Nile tilapia (Oreochromis niloticus) fingerlings were put in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…[14], confirmed the activity of protease enzyme (trypsin and chymotrypsin) was significant in three species of fish (Labeo rotita, Catla catal, and Hypophthalmichthys molitritx), due to the spread of the enzyme along the digestive tract. While the study by [15], also confirmed that the best activity of the protease enzyme was in fish fed a diet treated Oyster Mushrooms (Pleurotus ostreatus) in stimulating proteases of common carp fish, the best replacement was 66 % of date pit powder treated with mushrooms instead of yellow corn . This was confirmed by [16], when using dates pits treated with Oyster mushrooms( Pleurotus ostreatus) to stimulate protease enzymes in the intestinal of carp fish confirmed that the best replacement rate was 66 % of date pits treated with oyster mushrooms instead of yellow corn.…”
Section: Chymotrypsinmentioning
confidence: 82%
“…[14], confirmed the activity of protease enzyme (trypsin and chymotrypsin) was significant in three species of fish (Labeo rotita, Catla catal, and Hypophthalmichthys molitritx), due to the spread of the enzyme along the digestive tract. While the study by [15], also confirmed that the best activity of the protease enzyme was in fish fed a diet treated Oyster Mushrooms (Pleurotus ostreatus) in stimulating proteases of common carp fish, the best replacement was 66 % of date pit powder treated with mushrooms instead of yellow corn . This was confirmed by [16], when using dates pits treated with Oyster mushrooms( Pleurotus ostreatus) to stimulate protease enzymes in the intestinal of carp fish confirmed that the best replacement rate was 66 % of date pits treated with oyster mushrooms instead of yellow corn.…”
Section: Chymotrypsinmentioning
confidence: 82%